Perumpamaan dalam Hadis - Damanik, Damanik (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2013)
Hadith is a synonym of the Sunnah that according to the terminology is "everything that was taken from the Prophet Muhammad. before and after the appointed Apostle, either in the form of the word, deed or in the form of statutes (Taqrir). Total Sunnah or Hadith Apostle during his life very much, but a special phrase or "Word = اقوا ل" in the form of "Parables, amtsal or Metaphorically", not so many in number, but the tradition expressed in the form of a parable or the al-Amtsal, so has special impression in the hearts of those who listen and think about.